Amorphous molybdenum sulfide quantum dots: an efficient hydrogen evolution electrocatalyst in neutral medium - Dinda, Diptiman; Ahmed, Md. Estak; Mandal, Sumit; Mondal, Biswajit; Saha, Shyamal Kumar (Journal of materials chemistry. A, Materials for energy and sustainability, 2016)
To overcome the limitations of active edges, electrical conductivity and the surface area of MoS 2 nanosheets, in the present work, we have successfully synthesized amorphous MoS x quantum dots with a larger number of edge atoms using a simple chemical reaction via a bottom-up approach. Structural and chemical characterizations are carried out by TEM, XRD, Raman and XPS measurements. XPS and EDX analyses indicate a larger number of unsaturated ‘S’ atoms in these ultrafine amorphous quantum dots. We have used this material as an efficient electrocatalyst for the hydrogen evolution reaction (HER) in neutral medium. The material shows a remarkably low overpotential (65 mV) towards HER compared to that of other crystalline MoS 2 quantum dots or nanomaterials. The origin of such a low onset potential is the presence of more unsaturated sulfur (S 2 2− ) ligands and enhanced active edge sites. It also shows very high catalytic activity as well as good stability after 12 h of hydrogen generation in neutral water medium.